The Influence of Trust, Convenience and Risk on Decisions to Purchase Beauty Products Online Via E-Commerce (Case Study of UIN Raden Fatah Palembang Student) - Tanti Rosa Diyan Pratiwi; Mulyani Rizki; Safitri Asrol (Journal of Social Entrepreneurship and Creative Technology, 2024)
The purpose of this study was to analyze the influence of trust, convenience and risk on online beauty product purchasing decisions through e-commerce of UIN Raden Fatah Palembang students. This study uses a quantitative research design aimed at consumers or users of e-commerce shopee, tiktok shop and facebook on UIN Raden Fatah students. with a data collection method using a questionnaire. for sampling in this study in the form of probability sampling with a sampling technique using a simple random sampling technique of 100 people with the help of IBM SPSS 26 program analysis. The results of this study indicate that trust has a positive and significant effect on the decision to purchase beauty products through e-commerce. Convenience has a positive and significant effect on the decision to purchase beauty products through e-commerce. Risk has a positive and significant effect on the decision to purchase beauty products through e-commerce. Simultaneously, trust, convenience and risk together have a positive and significant effect on the decision to purchase beauty products online through e-commerce on UIN Raden Fatah Palembang students.